Which Countries Give Investors the Best Protection? - La Porta, Rafael (World Bank, Washington, DC, 2012)
Does the owner of a share of stock in Mexico have the same rights as one in Germany or India? Is a creditor in Italy as well protected as one in Switzerland? Do laws protecting investors differ among countries in systematic ways? Are they sufficiently enforced everywhere? And if there are differences, do they matter for corporate finance? This Note reports on a study by the authors that examines these issues in a sample of countries covering Asia, Africa, Europe, and North and South America. The analysis suggests that countries whose legal rules originate in the common law tradition tend to protect investors better than those whose laws originate in the civil law tradition, especially French civil law.